2010
DOI: 10.1007/s11266-010-9149-1
|View full text |Cite
|
Sign up to set email alerts
|

‘Doing Something Positive’: Volunteers’ Experiences of the Well-Being Benefits Derived from Practical Conservation Activities in Nature

Abstract: There is a strong tradition in Britain of volunteering involving a wide range of activities and organisations. Increasingly volunteering is seen as a way of benefiting health and building sustainable communities. In a study in 2007 we aimed to address the research questions: what are the motivations for, barriers to, and benefits of formal practical environmental volunteering for those individuals involved? Qualitative and quantitative data collection was undertaken while spending a day each with ten volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(87 citation statements)
references
References 16 publications
2
84
0
1
Order By: Relevance
“…It is important to note that barriers to participating in projects can be real or perceived (Unell and Castle 2012). For example, O'Brien et al (2010) researched barriers to environmental volunteering and found time pressures to be one of the most important. Lack of time is an important perceived barrier for many people, who believe that volunteering requires more time than they have to give (Unell and Castle 2012), although it is possible to design tasks within projects which require only small time commitments.…”
Section: Personal Attributes Circumstances and Demographicsmentioning
confidence: 99%
See 3 more Smart Citations
“…It is important to note that barriers to participating in projects can be real or perceived (Unell and Castle 2012). For example, O'Brien et al (2010) researched barriers to environmental volunteering and found time pressures to be one of the most important. Lack of time is an important perceived barrier for many people, who believe that volunteering requires more time than they have to give (Unell and Castle 2012), although it is possible to design tasks within projects which require only small time commitments.…”
Section: Personal Attributes Circumstances and Demographicsmentioning
confidence: 99%
“…O'Brien et al (2010) identify lack of information on opportunities for volunteering and a lack of understanding of what volunteering involves as key barriers to environmental volunteering. It is therefore vital to consider how potential participants will become aware of the opportunity.…”
Section: Awareness Of Opportunitymentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have examined park-based and conservation-oriented volunteer tourists (e.g., Cassie & Halpenny, 2003;Douglas & Rollins, 2007;Halpenny & Cassie, 2003;Measham & Barnett, 2008;O'Brien, Townsend, & Ebden, 2010;Ryan, Kaplan & Grese, 2001;Savanick Guiney & Oberhauser, 2009;Wearing & Neil, 2001). …”
Section: The Volunteersmentioning
confidence: 99%